Eco-friendly materials for heat pump hydraulic module plastic parts - Pinto, Nathália Magre Guerra (2023)
The present work focuses on identifying potential eco-friendly material alternatives for the hydraulic module of Bosch’s heat pumps, specifically in thermoplastic composite water guiding parts that composes the hydraulic module of the appliance. A benchmark was conducted with material suppliers to explore solutions with suitable mechanical and thermal properties that surpass the current material used in sustainability, with a particular emphasis on recycled or biobased options, and five materials were selected. Furthermore, a prototype part was produced through injection moulding in the selected alternatives and in the current material used on the module. The work encompasses a comprehensive evaluation of the prototypes, including dimensional analysis through manual measurements and CT Scanning, and a series of tests, including FEA static simulations, pressure robustness testing and pressure drop testing, conducted to compare the material’s performances. At the end, all the materials tested were considered suitable options, being EcoPaXX Q-DWX6 the most indicated one, outperforming the baseline. To finalize the comparative study, it is necessary to carry out the aging of the materials and reassess their performance under these conditions, in addition to measuring the impact of the appropriate alternatives regarding the reduction of the carbon footprint.